Pengaruh Stres Kerja dan Motivasi Kerja terhadap Kepuasan Kerja pada Satuan Polisi Lalu Lintas Polrestabes Makassar - Asty Almaida; Sigit Purnomo (Studi Ilmu Manajemen dan Organisasi, 2021)
Purpose: Indeed, the achievement of each organization's goals cannot be divorced from the performance of each individual member. Meanwhile, peak performance is strongly influenced by members of the organization's level of job satisfaction. Additionally, job satisfaction can be influenced by a variety of factors that can either increase or decrease members' level of job satisfaction. Thus, the purpose of this study was to ascertain the effect of job stress and motivation on job satisfaction at the Makassar Police Traffic Police Unit. Research methodology: The data for this study were derived from primary sources via questionnaires. This study surveyed 100 respondents. SEM-PLS analysis was used to conduct the analysis in this study. Results: The results indicate that work stress and motivation have no effect on job satisfaction. Limitations: It is hoped that additional researchers will be able to refine this research by examining additional construct variables in addition to those used to measure job satisfaction. Contribution: This study contributes to a better understanding of how work stress and motivation affect job satisfaction at the Makassar Police Department's Traffic Police Unit.